For host factors weddings and a Koch’s bacillus funeral: actin, lipids, phagosome maturation and inflammasome activation - Anes, Elsa (2013)
The chapter describes the 10 years research of Anes Laboratory on the interactions of M. tuberculosis with macrophages namely with the actin. modulation by lipids, phagosome maturation and inflammasome activation